Is transportation a risk factor for African swine fever transmission in Australia: a review - Neumann EJ; Hall WF; Dahl J; Hamilton D; Kurian A (John Wiley and Sons Australia, Ltd on behalf of Australian Veterinary Association, 2021)
African swine fever (ASF) is a viral disease of the pigs that was first described in Africa during the early part of the twentieth century. The disease has periodically occurred outside of Africa, including an ongoing epidemic in Europe and Asia that started in 2007; the disease has never occurred in Australia or New Zealand. Once introduced into a country, spread can occur through direct and indirect routes of transmission. Infected feral pig populations have the potential to act as a long-term reservoir for the virus, making eradication difficult. Just before and throughout the period of clinical signs, ASF virus is shed in oronasal fluids, urine, faeces and blood. This results in contamination of the pig's environment, including flooring, equipment and vehicles. Transportation-related risk factors therefore are likely to play an important role in ASF spread, though evidence thus far has been largely anecdotal. In addition to the existing AUSVETPLAN ASF plan, efforts should be made to improve transportation biosecurity, from the time a pig leaves the farm to its destination. Collection of data that could quantify the capabilities and capacity of Australia to clean and disinfect livestock trucks would help to determine if private and/or public sector investment should be made in this area of biosecurity. No peer-reviewed research was identified that described a specific process for cleaning and disinfecting a livestock truck known to be contaminated with ASF virus, though literature suggests that transportation is an important route of transmission for moving the virus between farms and countries.
Keywords: African swine fever; biosecurity; epidemiology; pig; risk factors; transportation; African Swine Fever; African Swine Fever Virus; Animals; Disease Outbreaks; Risk Factors; Sus scrofa; Swine; Swine Diseases